Conjoined thoracopagus twins - Our experience of successful separation - Arvind Sinha; Rahul Saxena; Manish Pathak; Mahaveer Singh Rodha (Wolters Kluwer Medknow Publications, 2021)
Conjoined twin is an extremely rare condition and needs a thorough knowledge of anatomy and a multidisciplinary approach is essential to successfully separate, the twins. Thoracopagus are the twins attached by chest and umbilicus and are the commonest among all the varieties but carries a poor survival rate. We describe our approach and experience of management of thoracopagus twins who were separated at eighty-three day of life and are alive and well after 4 years of follow up. The most important decisive parameter for successful separation is the extent of sharing of organs between twins but the role of a motivated multidisciplinary team is also indispensable.